2021
DOI: 10.1007/s40801-021-00284-1
|View full text |Cite
|
Sign up to set email alerts
|

Falls and Fractures in Patients with Parkinson’s Disease-Related Psychosis Treated with Pimavanserin vs Atypical Antipsychotics: A Cohort Study

Abstract: Background Parkinson’s disease-related psychosis increases patients’ risk of falls. Pimavanserin is an atypical antipsychotic approved in the USA in 2016 for the treatment of hallucinations and delusions associated with Parkinson’s disease-related psychosis. Objective We aimed to compare the risk of falls/fractures among patients with Parkinson’s disease-related psychosis treated with pimavanserin vs other atypical antipsychotics. Patients and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…When comparing users of relatively newly marketed medications to users of an established class of medication(s), users of the newer treatments may differ in systematic ways, which may be difficult to predict [ 36 ], resulting in confounding. Consistent with patterns observed in other studies of pimavanserin users compared with users of other atypical antipsychotics [ 17 , 37 ], the pimavanserin users in the present study generally had fewer comorbidities, and a higher proportion of patients used anti-Parkinson drugs and had their index antipsychotic prescribed by a neurologist. To account for confounding by differences in frailty, access to health care, health-seeking behavior, and other differences between groups, this study balanced treatment groups with respect to demographic, clinical, and health-care utilization variables through PS matching; almost all pimavanserin users were successfully matched, and all measured baseline characteristics were very well balanced after matching.…”
Section: Discussionsupporting
confidence: 90%
“…When comparing users of relatively newly marketed medications to users of an established class of medication(s), users of the newer treatments may differ in systematic ways, which may be difficult to predict [ 36 ], resulting in confounding. Consistent with patterns observed in other studies of pimavanserin users compared with users of other atypical antipsychotics [ 17 , 37 ], the pimavanserin users in the present study generally had fewer comorbidities, and a higher proportion of patients used anti-Parkinson drugs and had their index antipsychotic prescribed by a neurologist. To account for confounding by differences in frailty, access to health care, health-seeking behavior, and other differences between groups, this study balanced treatment groups with respect to demographic, clinical, and health-care utilization variables through PS matching; almost all pimavanserin users were successfully matched, and all measured baseline characteristics were very well balanced after matching.…”
Section: Discussionsupporting
confidence: 90%
“…A recent cohort study after sensitive statistical analysis demonstrated a decreased risk of falls and fractures in patients with PD psychosis treated with PMV versus atypical antipsychotics [ 64 ]. The incidence ratio estimated was 0.55 (95% CI 0.34–0.86).…”
Section: Pimavanserin Clinical Experiencementioning
confidence: 99%
“…The number of patients seen or followed was not published, but as of June 22, 2022, the same clinic was treating 43 of 5080 distinct patients with PD with clozapine (M. Okun, personal communication). A report analyzing more than 3300 patients with PD aged 40 years and older and treated for psychosis with antipsychotic drugs in the database of Optum 30 from 2001 to 2019 found that “clozapine was too rare to include in our statistical analyses.” Layton et al 31 evaluated patients in a large data set who met clearly defined inclusion criteria for PDP and identified 982 taking antipsychotics, of whom less than 1% were treated with clozapine. Using a different database covering 2016 to 2019, the same researchers 32 identified 2892 PDP treated with pimavanserin and compared them with 19,083 matched comparators treated with atypicals, of whom 37 were on clozapine.…”
Section: Underusementioning
confidence: 99%